Determination of major and trace elements in different parts of various medicinal plants with therapeutic effect retaile groing in middle atlas of morocco using icp-oes - Jadouali, S. M.; Atifi, H.; Ibourki, M.; Ait bella, Y.; Khadfy, Z.; Benaziz, M.; Benali, T.; Gharby, S.; Mamouni, R. (International Journal of Agricultural Technology, 2024)
The elemental composition of fifteen species of medicinal plants growing in the middle atlas of Morocco was determined by ICP-AES. Among major and minor elements, K with a content in the ranged of 4471,97- 20862,43 mg/kg and Fe in the ranged of 20457,45 - 3310,69 mg/kg are the most presented in the analysed species. The highest concentrations of the analyzed elements were found as follows: Ca in Mentha pulegium L., Na in Atractylis gummifera, K, Mg and Fe in Herniaria hirsuta, Mn in Daphne gnidium, Cu in Thymus willdenowii, Zn in Corrigiola telephiifolia,B in Pistacia lentiscus L., P in Lepidium sativum, P in Saw palmetto .Similarly, the lowest levels were found as follows: Ca, Na, Fe, Mn, Cu, Zn and Mg in Saw palmetto, K and S in Tetraclinis articulata, B in Lepidium sativum, P in Aristolochia paucinervis. Significant correlations were observed between the various minerals. The results showed that the analysed plants are constituted a new and interesting source of minerals indispensable for human nutrition and for pharmaceutical purposes and for the treatment of diseases.